Geometria fractal : da natureza para a sala de aula - Ferreira Filho, José Roberto (2015)
This work deals with the study of fractal geometry, emphasizing its main features included on natural systems that motivate them. Here some names that contributed to the emergence and development of mathematical fractals, emphasizing examples of natural fractals and the pioneer of Benoit B. Mandelbrot contribution .